Representation of Victim and Perpetrator in Adelina Lisao’s Abuse Case in Malaysian Online News Articles - binti Adanan, Aizatul Alyaa; binti Ungku Mohd Nordin, Ungku Khairunnisa (Indonesian Journal of Social Science Research, 2024)
This research analyses the representation of victim and perpetrator as social actors and its argumentation strategies from Malaysian online news articles surrounding the tragic case of Adelina Lisao, an Indonesian domestic worker who lost her life in Malaysia due to abuse by her employer. Employing a qualitative research approach, the data is systematically collected with keywords to identify relevant news articles pertinent to the case: "Adelina Lisao” and “Ambika Shan”. This research utilises the Social Actor’s Network (SAN) and the Critical Discourse Analysis (CDA) framework, specifically the Discourse-Historical Approach (DHA), to examine 39 online news articles about the case from the most popular Malaysian news website in 2023, Malaysiakini. The findings revealed that Adelina Lisao was mostly represented as a passive receiver of the abuse, while Ambika Shan’s role as a perpetrator was mostly backgrounded. The findings contribute to a better understanding of how social actors are portrayed on online websites and the argumentation strategies within the context of domestic worker abuse cases in Malaysia. Thus, it acknowledges the importance of language in online news discourse in shaping public perceptions, particularly regarding domestic workers in Malaysia as evidenced by the representation of victim-perpetrator dynamics in such cases.